Retrospective clinical analysis of time to recovery from diabetic ketoacidosis in Ethiopia - Angefa Ayele; Dube Jara; Alo Edin; Digafe Hailu; Mihiret Kifle; Yohannes Fekadu (Endocrine and Metabolic Science)
Background: Diabetes is a metabolic disorder that affected > or = 500 million people in 2021. Diabetic ketoacidosis is the most serious acute complication. Because of the significant health burden of diabetic ketoacidosis, we performed a retrospective study on the recovery time and predictors among adult diabetic mellitus patients in selected public hospitals in Southern Oromia in Ethiopia. Methods: A retrospective follow-up study was conducted of 316 randomly selected adult diabetic ketoacidosis patients admitted between January 1, 2020, and July 31, 2023. A structured checklist was utilized. Data were entered into Epi-data version 4.6 and analyzed with STATA version 17, employing Kaplan-Meier survival curves, log-rank tests, and Cox-proportional hazards models to identify predictors. Results from bivariable and multivariable Cox-regression were reported via adjusted hazard ratio with 95 % confidence intervals. Results: This study included 316 participants, with 256 adults (81.01 %) recovering throughout the follow-up period. The overall DKA recovery rate was 23.8 per 1000 person-hours (95 % CI: 22.21–27.07), and the median recovery time was 42 hr. Significant predictors of recovery time included random blood glucose level [AHR (95 % CI): 0.58 (0.38–0.90)], duration of diabetes mellitus [AHR (95 % CI): 0.24 (0.14–0.69)], and severity of DKA [AHR (95 % CI): 0.46 (0.16–0.84)]. Conclusion: The median DKA recovery time was prolonged, increasing the risk of complications. Blood glucose level, diabetes duration, and DKA severity were predictors of recovery time. Therefore, targeting these factors through research and interventions may improve outcomes and reduce DKA recovery duration.